2017
DOI: 10.1002/berj.3280
|View full text |Cite
|
Sign up to set email alerts
|

Storied emotional distances in the relationships between beginning teachers and school principals

Abstract: Recent research has acknowledged the importance of the relationships of school principals with beginning teachers. However, little is known about how emotions inform these relationships from the beginning teacher's side. Applying the concept of emotional geographies, this paper explores the kinds of storied emotional distances that appear in the relationships between beginning teachers and their principals. Based on interviews with beginning Japanese teachers, the results indicate that such relationships may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…School principals’ position, indeed, is at the crossroad between a helping profession and a public administration role [ 24 , 25 , 26 , 27 , 28 , 103 ]. This duality influences the way principals perceive their work experiences, likely influencing their professional and personal identity [ 29 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…School principals’ position, indeed, is at the crossroad between a helping profession and a public administration role [ 24 , 25 , 26 , 27 , 28 , 103 ]. This duality influences the way principals perceive their work experiences, likely influencing their professional and personal identity [ 29 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature, indeed, showed that relationships at work highly contribute to shaping the meaning of work, by addressing peer connections (Wrzesniewski et al , 2003; Kahn, 2007), as well as relationships with supervisors (Podolny et al , 2004; Piccolo and Colquitt, 2006) and the extended work community (Wrzesniewski et al , 2003; Grant et al , 2008). This point may be particularly relevant for school principals, too, as they are required to manage several relationships because of their leadership position: from colleagues in professional associations (Relja et al , 2019) to teachers and other school staff members (Ponec and Brock, 2000; Lassila et al , 2017), from students to their families (Lam, 2000; Quezada, 2016). This plurality requires principals to differently perceive and manage their role at school according to their interlocutors, thus shaping the meaning of their job at school.…”
Section: Discussionmentioning
confidence: 99%
“…If "specialized training is not provided for principals to garner such skills, they will continue to be at a disadvantage regardless of how good their intentions are" (Baker-Gardner, 2015, p. 58). Furthermore, in training educational leaders, relationships should be discussed and problematized to raise awareness of the influence of a principal' s words and actions on teachers' work (Lassila, Timonen, Uitto, & Estola, 2017). The generous insights from the stories shared through this interview process of a cross-section of early career teachers across Canada, enrich our understanding of their experiences with leadership and supports from school administration in the formative years of their careers.…”
Section: Discussion Of Findingsmentioning
confidence: 99%